Constitutionality of Restrictions on the Right to Freedom of Speech in the Digital Era from a Constitutional Law Perspective - Adianto Mau, Hedwig (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study aims to analyze the constitutionality of restrictions on the right to freedom of expression in the digital era from the perspective of constitutional law. Freedom of expression is a fundamental human right guaranteed by the Indonesian Constitution, as stated in Article 28E paragraph (3) of the 1945 Constitution of the Republic of Indonesia. However, the exercise of this right is not absolute and may be limited as stipulated in Article 28J of the 1945 Constitution. In the context of the digital era, various regulations have emerged, such as the Electronic Information and Transactions Law (UU ITE), which often serves as an instrument to restrict digital expression. This research uses a normative juridical method with statutory, conceptual, and case approaches. The results of the study show that freedom of expression in the digital era is a constitutional right essential to democratic life, but its implementation in Indonesia still faces challenges. Although guaranteed by the 1945 Constitution and various legal instruments such as the Human Rights Law and the ITE Law, its implementation often sparks controversy due to multiple interpretations and the potential misuse of certain articles to limit expression, especially in digital spaces. From the perspective of constitutional law, restrictions on freedom of expression are permissible but must fulfill the principles of legality, proportionality, and urgent necessity, and should not be used to silence criticism. Therefore, a fairer and clearer regulatory revision is needed, along with cooperation between the government, civil society, and stakeholders to create a safe, inclusive, and democratic digital space